2017
DOI: 10.1007/s11912-017-0619-0
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Inhibitors for Non-Small Cell Lung Cancer Among Older Adults

Abstract: Non-small cell lung cancer (NSCLC) is mostly a disease of older adults, with its incidence and mortality rates increasing exponentially after the age of 65 years. Immune checkpoint inhibitors (ICIs) have changed the scene of NSCLC treatment after a long and relatively stagnant period of standard treatment regimens. However, little is known about the specific impact of these agents in older adults for whom care is often complicated by a variety of syndromes. This underlines the importance of understanding the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 109 publications
1
19
0
Order By: Relevance
“…No differences were observed in terms of PFS, OS and frequency of irAEs when compared with a cohort of younger patients (≤74 years old) who received a parallel treatment in the same time period. These data are in line with the results of previous studies reporting the efficacy and the safety of anti-PD-1 and anti-PD-L1 mABs in elderly patients [20][21][22][23]. The majority of these studies, however, chose a cut-off of 65 years according to the international guidelines and may not clearly reflect the actual elderly population affected by lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…No differences were observed in terms of PFS, OS and frequency of irAEs when compared with a cohort of younger patients (≤74 years old) who received a parallel treatment in the same time period. These data are in line with the results of previous studies reporting the efficacy and the safety of anti-PD-1 and anti-PD-L1 mABs in elderly patients [20][21][22][23]. The majority of these studies, however, chose a cut-off of 65 years according to the international guidelines and may not clearly reflect the actual elderly population affected by lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Studies of cancers diagnosed and deaths by age-group show that elderly patients (≥65 years) are overrepresented with a further increase expected over the next decade, eg, data with NSCLC. 72 Yet this population is quite underrepresented in clinical trials, and it has been known for many years that aging per se is reflected in many changes in immunity, both qualitative and quantitative. 73 , 74 As more attention is paid to this discrepancy, we can anticipate an improved understanding of checkpoint blockade in aging, more specific clinical trials for elderly cancer patients, and an improved “juggling” of combination immunotherapies to improve cancer survival across multiple disease types.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to explore the survival benefit of immunotherapy in elderly patients because an increase in age is usually accompanied with a decline in functions of the immune system, especially the T cell-mediated immune defense system, resulting in a poor efficacy of immune checkpoint inhibitors for the treatment of elderly patients (21). Other studies have shown that aging may not affect the effectiveness of immunotherapy (22)(23)(24). In the current study, we included nine NSCLC patients aged over 70 years old and found that two of them reached a PR and five reached SD, indicating that there was no significant difference in the benefit of such a treatment in older patients compared with younger patients.…”
Section: Discussionmentioning
confidence: 99%